Cancer, coping, and cognition: a model for the role of stress reactivity in cancer‐related cognitive decline. Issue 6 (6th October 2014) - Andreotti, Charissa; Root, James C.; Ahles, Tim A.; McEwen, Bruce S.; Compas, Bruce E.
Abstract Background Cognitive decline and accompanying neurological changes associated with non‐CNS cancer diagnosis and treatment have been increasingly identified in a subset of patients. Initially believed to be because of neurotoxic effects of chemotherapy exposure, observation of cognitive decline in patients not treated with chemotherapy, cancer‐diagnosed individuals prior to treatment, and patients receiving alternative treatment modalities (surgery, endocrine therapy, and radiation) has led to the investigation of additional potential etiologies and moderating factors. Stressful experiences have long been posited as a contributor to these cognitive changes. Through reciprocal connectivity with peripheral systems, the brain maintains a dynamic circuitry to adapt to stress (allostasis). However, overuse of this system leads to dysregulation and contributes to pathophysiology (allostatic load). At this time, little research has been conducted to systematically examine the role of allostatic load in cancer‐related cognitive dysfunction. Methods and Results Here, we integrate theories of stress biology, neuropsychology, and coping and propose a model through which individuals with a high level of allostatic load at diagnosis may be particularly vulnerable to the neurocognitive effects of cancer. Conclusions Opportunities for future research to test and extend proposed mechanisms are discussed in addition to points of prevention and intervention based on individual variation in stress reactivity and coping skills. Copyright © 2014 John Wiley & Sons, Ltd.